A long-reach WDM passive optical network enabling broadcasting service with centralized light source - Fu, Songnian (2013)
We propose a long-reach wavelength-division-multiplexed (WDM) passive optical network (PON) to provide conventional point-to-point (P2P) data and downstream broadcasting service simultaneously by superimposing, for each WDM channel, the differential-phase-shift-keying (DPSK) broadcasting signal with the subcarrier multiplexing (SCM) modulated downstream P2P signal, at the optical line terminal (OLT). In the optical network units (ONUs), by re-modulating part of the downstream signal with a reflective semiconductor optical amplifier (RSOA), we realize color-less ONUs for upstream data transmission. The proposed scheme is numerically verified with a 5 Gb/s downstream P2P signal and broadcasting services, as well as 2.5 Gb/s upstream data through a 60 km bidirectional fiber link. In particular, the influence of the downstream lightwave's optical carrier–subcarrier ratio (OCSR) on the system performance is also investigated.